Macrophages promote osteoblastic differentiation in‐vivo: implications in fracture repair and bone homeostasis. (June 2015) - Vi, Linda; Baht, Gurpreet S; Whetstone, Heather; Ng, Adeline; Wei, Qingxia; Poon, Raymond; Mylvaganam, Sivakami; Grynpas, Marc; Alman, Benjamin A
ABSTRACT Macrophages are activated in inflammation and during early phases of repair processes. Interestingly, they are also present in bone during development, but their function during this process is unclear. Here, we explore the function of macrophages in bone development, growth, and repair using transgenic mice to constitutively or conditionally deplete macrophages. Depletion of macrophages led to early skeletal growth retardation and progressive osteoporosis. By 3 months of age, macrophage‐deficient mice displayed a 25% reduction in bone mineral density and a 70% reduction in the number of trabecular bone compared to control littermates. Despite depletion of macrophages, functional osteoclasts were still present in bones, lining trabecular bone and the endosteal surface of the cortical bone. Furthermore, ablation of macrophages led to a 60% reduction in the number of bone marrow mesenchymal progenitor cells and a decrease in the ability of these cells to differentiate to osteoblasts. When macrophages were depleted during fracture repair, bone union was impaired. Calluses from macrophage‐deficient animals were smaller, and contained less bone and more fibrotic tissue deposition. Taken together, this shows that macrophages are crucial for maintaining bone homeostasis and promoting fracture repair by enhancing the differentiation of mesenchymal progenitors. © 2014 American Society for Bone and Mineral Research.